2002
DOI: 10.1902/jop.2002.73.10.1141
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Simvastatin Gels on Murine Calvarial Bone

Abstract: A single, high dose of simvastatin gel can stimulate murine cranial bone apposition, particularly when delivered under an occlusive membrane. Both approaches should be investigated further for possible development for periodontal therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
137
2
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(154 citation statements)
references
References 32 publications
10
137
2
5
Order By: Relevance
“…The same occurred with the osteoclasts with greater scores in the simvastatin group compared with the control group. These results are in agreement with other studies [16][17][18][19]26 . In the late period of regeneration, simvastatin was able to stimulate a greater presence of osteoblasts and subsequent bone formation.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The same occurred with the osteoclasts with greater scores in the simvastatin group compared with the control group. These results are in agreement with other studies [16][17][18][19]26 . In the late period of regeneration, simvastatin was able to stimulate a greater presence of osteoblasts and subsequent bone formation.…”
Section: Discussionsupporting
confidence: 94%
“…Other reports indicate that simvastatin 17,[25][26][27][28] influenced and stimulated new bone formation. There are few consistent studies on the anabolic effects and bioavailability of simvastatin, which is a fact that leads to such varying results among several studies 29 .…”
Section: Immunohistochemistry Evaluationmentioning
confidence: 94%
“…4 In the present study, the use of high local doses of simvastatin caused an intense inflammatory reaction, accompanied by tissue necrosis and scabbing. Soft tissue inflammation was also reported by Thylin et al, 6 who used 2.2 mg of the drug in methylcellulose gel in rat calvaria; by Nyan et al, 9 who used 1 mg of the drug in calcium sulfate in rat calvaria; and by Stein et al, 7 who used doses of 0.5, 1.0, 1.5, and 2.2 mg of the drug in rat mandible. In the study conducted by Stein et al, 7 the 0.5-mg dose presented the best cost-benefit ratio, promoting significant bone formation and reduced inflammation.…”
Section: Discussionmentioning
confidence: 61%
“…• local delivery in methylcellulose gel; 6,7 • local delivery in polylactic acid/polyglycolic acid copolymer; 5 • local delivery in gelatin sponge; 8 and • statins used in combination with calcium sulfate. 9,10 The results have often been encouraging.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, implant insertion was in the present study mono-cortical while Du et al performed bi-cortical insertion. Since the successful local application of statins has been demonstrated to depend on an effective drug delivery system, like chitosan, PGA or methylcellulose gels (Thylin et al, 2002), we have utilised chitosan in the present study. In accordance with previous studies, we observed a transient increase in BIC and the amount of peri-implant bone in the group that had received statin coated implants.…”
Section: B Stadlinger Et Al Modified Implants In An Osteoporosis Modelmentioning
confidence: 99%